Modelling the influence of daytime distribution on the transport of two sympatric krill species (Thysanoessa raschii and Meganyctiphanes norvegica) in the Gulf of St Lawrence, eastern Canada - Maps, Frédéric; Plourde, Stéphane; Lavoie, Diane; McQuinn, Ian; Chassé, Joël (ICES Journal of Marine Science, 2014)
<qd> Maps, F., Plourde, S., Lavoie, D., McQuinn, I., and Chassé, J. 2014. Modelling the influence of daytime distribution on the transport of two sympatric krill species ( Thysanoessa raschii and Meganyctiphanes norvegica ) in the Gulf of St Lawrence, eastern Canada. – ICES Journal of Marine Science, 71: 282–292. </qd>The Gulf of St Lawrence (GSL) provides several species of North Atlantic baleen whale with an abundant supply of krill, dominated by Thysanoessa raschii and Meganyctiphanes norvegica . We aimed to quantify the differences in upstream advection resulting from the interaction between the circulation and the specific diel vertical migration of T. raschii and M. norvegica at the scale of the northwest GSL. We coupled a regional circulation model with Lagrangian models where the daytime depth followed specific functions of surface salinity. Our results help to explain the spatio-temporal variability in both T. raschii and M. norvegica distributions. We identified in particular spatio-temporal patterns in krill upstream transport. During summer and autumn, the upstream transport of krill is steady across Jacques Cartier Strait, limited across Honguedo Strait, and more sporadic across the Estuary mouth. We estimated that the upstream advection of krill particles across the Estuary mouth would be higher by 16–17% for the T. raschii than for the M. norvegica daytime behaviour. Our results also suggest that the advective processes operating on the adults during the productive season are not the only cause for the observed magnitude of the interannual and interspecific variability in krill abundance.